ETR 300 : Primera Robusta Factory / Amirul Ashraff Mahamad ... [et al.] - Mahamad, Amirul Ashraff; Ramli, Rozana; Sukor, Ruzi; Paharurrazi, Nur Haida; Mohd Faudzi, Norhasriza Farazila (2003)
Starting and planning a new business requires a lot of effort either in materials or time consuming and not to mention a quite level of risk to create and develop something new in the market. Once an entrepreneur enter the market, he may exposed to the responsibilities and risks to build up their own brand, ensure the survival of the business and finally enjoys the rewards after all efforts have been contributed to the business. The consumers, business communities and government plays a related roles in boosting the entrepreneurship whether in research and development, increment of the course at the universities and held seminars to the fresh entrepreneurs on how to develop and in furtherance control the market.